Audit of ophthalmological case management: a case series review at a local health clinic - Shalihin, Mohd Shaiful Ehsan; Mohd Asri, Nur Azrin Farhana (UniKL Royal College of Medicine Perak (UniKL RCMP), 2024)
Eye diseases are among the common cases encountered in health clinics. They range from stable to unstable cases. Nevertheless, there are still unclear approaches taken by health care providers in treating them, especially in relation to urgent referrals or outpatient care requirements. We conducted an audit at a local health clinic involving eye cases encountered in the treatment room, which had been assigned as an emergency during the afternoon session for one week. Of the 68 cases recorded, seven involved eyes. The majority were foreign body cases, which were not referred to ophthalmological care and were not preceded by eye irrigation. Therefore, in-house training on the approach to eye diseases should be conducted from time to time.